Pengembangan Media PARO (papan romawi) pada Mata Pelajaran Matematika Materi Bilangan Romawi Kelas IV SD - Anggit Aziz Riantono (Universitas Ahmad Dahlan, 2022)
This study aims to: (1) develop PARO media (roman board) on roman numerals, and (2) determine the quality and appropriateness of PARO media (roman board) as a learning media for mathematics learning materials for Roman numerals for grade IV elementary schools. This study uses R&D (Research and Development) research. The steps are 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product testing, 7) product revision, 8) product use trial, 9) design revision. This research was conducted at SD N Banyurejo 1 by using a sample of 6 fourth grade students and 16 fourth grade students. The data collection instrument used a questionnaire. Data analysis used qualitative and quantitative data analysis. The research subjects were grade IV teachers and 22 students at SD N Banyurejo 1. The results of the development were PARO (roman board) media in mathematics subject matter Roman numerals for grade IV elementary schools. Media PARO (roman board) was validated by 76 material experts with the category (Eligible), 85.5 media experts with the category (Very Appropriate), and 78.3 learning experts with the category (Eligible). The first trial obtained 100 in the (Very Eligible) category. The second trial obtained 97.7 with the category (very feasible). The results of the response of students on average from trials I and II were 98.7 with the category (Very Eligible). Teacher assessment obtained 93.8 with the category (Very Eligible). These results indicate that the PARO media (roman board) is suitable for use in the learning process in a very feasible category.